Metabolites produced by microalgae from northeastern Brazil with potential food industry uses (Research, Society and Development, 2022)
The production potential of metabolites of interest to the food industry was evaluated in 17 microalgae species isolated from natural sources in northeastern Brazil. The species were cultivated to their stationary phase under controlled conditions, when the experiments were interrupted and the dry biomass harvested. We observed differences in their growth parameters, productivity, and the biochemical compositions of their biomasses, with high levels of protein productivity in Monoraphidium litorale D296WC (48.96%), Kirchneriella concorta D498WC (42.49%), Monoraphidium griffithi D499WC (48.37%), Chlamydomonas sp. D530WC (44.80%), and Cosmarium sp cf. depressum D578WC (49.32). The greatest carbohydrate productivities were observed in Xanthonema sp. D464WC (34.15%), K. concorta D498WC (38.95%), and Scenedesmus acuminatus D514WC (36.54%). The three different extraction techniques of microalgae lipids all gave slightly different results, with the method utilizing phospho-vanillin being considered the most rapid and it requires only small quantities of biomass. Unsaturated fatty acids (oleic, linoleic, and linolenic) were encountered at high levels in most of the species, especially α-linolenic acid (ω3), which reached concentrations above 30% in Golenkinia radiata (D325WC). Due to their high productivity, rapid growth, and the large numbers of important dietary metabolites they produce, the species Monoraphidium litorale (D296WC), Xanthonema sp. (D464WC) and Monoraphidium griffithi (D499WC) show significant potential for utilization by the food industry as sources of proteins, lipids, and carbohydrates.